Concerns and Consequences of Industrial Livestock and Meat Production - Muthukumar, M.; Mandal, P. K. (Journal of Meat Science, 2018)
Meat has been consumed as a part of diet since pre-historic times and the fast growing population fuelled greater demand for meat and meat production. This led to gradual drive in modern livestock farming towards increased productivity and intensification. In the intensive farming, use of large numbers of chemicals/drugs to control or prevent infections or to promote more growth has become inevitable. When animals are treated with veterinary medicines according to the licensed conditions of dose, period of treatment and withholding period specified before slaughter, residues should be at levels that will not cause any effect on consumer health. However, improper and unethical use of various chemicals resulted in accumulation of unnatural substances in the meat food chain. The continuous consumption of meat and meat products contaminated with toxic residues induce changes in biotransformation of endogenous and exogenous compounds resulting in variety of health problems, particularly endocrine dysfunction, carcinomas and neurological disorders. Though traditional and natural methods of rearing of livestock is largely practiced in India, public awareness campaigns are urgently needed to alert farmers and professionals about the negative consequences of such misuse of drugs in animal on public health. On-farm practices and possible misuses of veterinary drugs need to be investigated to identify the source of such substances in carcasses. Detection and quantification of the drugs residues are also required to identify the main groups of veterinary drugs incriminated to improve the control system and the awareness at destination of stakeholders involved in the livestock farming and marketing sector. This article discusses about various issues related to antibiotics and hormones employed for growth promotion in meat animal production.
Keywords: Meat animal production; Antibiotics; Anti-bacterials; Growth promoters